Preparation of Microcapsules of Slow-Release NPK Compound Fertilizer and the Release Characteristics - Pang,Wancheng (2018)
In this study, a novel type of slow-release fertilizer (SRF) was synthesized through lignin-based microcapsules. K2HPO4 and urea were coated by lignin and formaldehyde to prepare microcapsules of NPK compound SRF. The slow-release performance was measured by determining the NPK contents in water solution and soil column leaching. The release amounts of N, P and K after 5 days were 95.39, 95.28 and 96.75% in water, and 83.35, 96.62 and 90.75% in soil, respectively. The properties of SRF were analyzed by Fourier transform infrared spectroscopy, thermogravimetry and scanning electron microscopy. NPK release from the SRF was promoted by higher temperature and acid environment, but inhibited by alkaline environment. The first order kinetics equation provides the best correlation to describe nutrient release characteristics. The results indicated that SRF have good slow-release properties and are cost-saving and environment-friendly, and thus can efficiently improve the utilization efficiency of fertilizers in agricultural production.